IMPLEMENTATION OF THE TREFFINGER MODEL BASED STEM APPROACH TO STUDENTS’ CREATIVE THINKING SKILL - Eni Lestari; Sofwan Hadi (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
Creative thinking can encourage students to solve problem. Learning Treffinger model provides opportunities for students to understand the concept through the process of solving problems creatively. The approach used to support this model is STEM approach. STEM learning that encourages increased thinking skills creative. This research aims to determine the implementation learning with the STEM-based Treffinger model, the application of the Treffinger model based STEM on creative thinking skills, and factors that affect learning. This research uses an approach quantitative and using Quasi Experiment with the Posttest-only Design with Noneequivalent Group. Population that used are students of class VIII at SMP Ma'arif 1 Ponorogo total of 84 students. The reseach sample from control class was 28 students and from the experimental class a total of 29 students. Data analysis techniques that used are independent test sample t test. Based on the data analysis, it was found that (1) implementation of the Treffinger model learning based on STEM is carried out very well, (2) the ability to think creatively in the class that applies the model STEM-based Treffinger is better than non-implemented the model, (3) the teacher's ability to deliver the subject matter and students who play an active role have an important role in the implementation conducive learning.